The Urgency Of Love Education: "Reading The Hadith On The Prohibition Of Adultery (A Dialogue Story Between Prophet Muhammad Saw And A Youth - Kusnan, Kusnan (Journal of World Science, 2022)
Adultery is a major sin after shirk to Allah swt. Adultery, besides being threatened with severe punishment and other punishments in the realm of barzah and mahsyar, will also have a very negative impact on social life. At the time of the Prophet there came a young man with a very high sexual libido, who vowed to like the Prophet and also to like Islam but asked that he be allowed to continue to commit adultery. This phenomenon was known by the companions of the Prophet and they sneered and some even shouted in an angry tone. Then the Prophet asked the companions to calm down, asked the youth to come closer (some narrations) so that the youth would enter the Prophet's house. Then the prophet gave advice with gentleness, full of empathy, love and intimacy. The dialogue between the prophet and the young man who asked for adultery took place warmly, meltingly, unlike when the young man was near (among) the companions. This phenomenon also implies the basic essence of education to mankind. From the results of the dialogue, finally the young man who used to have a very high sexual libido and always wanted to commit adultery, realized he was full of awareness and sincerely left adultery, condemned the act of adultery and did not want to glance at it at all.